2014
DOI: 10.1515/entl-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Cerium dioxide nanoparticles selectively up-regulate C-C chemokine receptor 2 and CD16 expression on human monocytes

Abstract: Cerium dioxide nanoparticles (CeO2 NPs) are known as scavengers of reactive oxygen species for the coexistence of Ce 3+ / Ce 4+ oxidation states. Cell treatments with CeO2 NPs often lead to controversial proinflammatory and anti-inflammatory results. The aim of the study was to investigate the immune events following the administration of ceria nanoparticles to THP-1 monocytes. To address this issue, we performed flow cytometry, chemotaxis and ELISA experiments on THP-1 monocytes treated with different concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Indeed, recent observations with gold nanoparticles (AuNPs) reported that these particles phagocytized by immune cells can retard the sensitivity of some immune responses [92]. This is not true for all NPs, in fact, some NMs have been proved not only to release inflammatory mediators including chemokines, but also to stimulate the up-regulation of particular chemokine receptors involved in many processes of inflammation [93].…”
Section: Figure 1 Schematic Representation Of Cellular Targeting Expl...mentioning
confidence: 99%
“…Indeed, recent observations with gold nanoparticles (AuNPs) reported that these particles phagocytized by immune cells can retard the sensitivity of some immune responses [92]. This is not true for all NPs, in fact, some NMs have been proved not only to release inflammatory mediators including chemokines, but also to stimulate the up-regulation of particular chemokine receptors involved in many processes of inflammation [93].…”
Section: Figure 1 Schematic Representation Of Cellular Targeting Expl...mentioning
confidence: 99%
“…Multiple-parameter analysis can also be performed using multiplex systems [ 88 , 108 , 109 ]. Cytokine release represents a key activity of immune cell to coordinate either inflammatory or anti-inflammatory responses.…”
Section: In Vitromentioning
confidence: 99%
“…Along with these well-known markers, the expression of membrane receptors involved in the cellular immune response can give the researcher important information [ 88 , 108 ]. Membrane proteins, as well as lipids, denote the activity of cells in the different physiological or pathological conditions.…”
Section: In Vitromentioning
confidence: 99%